Risk factors assessment of breast cancer among Iraqi Kurdish women: Case-control study - Hawar Hasan Ali Ghalib; Dawan Hiwa Ali; Sherko Abdullah Molah Karim; Mohammed Ibrahim Mohialdeen Gubari; Saman Ahmed Mohammed; Diyar Hassan Marif; Hawsar Mohammed Othman (Journal of Family Medicine and Primary Care, 2019)
Background: To our knowledge, there is no international publication on risk factors of breast cancer among Kurdish women. There are several risk factors of breast cancer may differ in different geographical cultures. The aims of this study are to assess the established and probable risk factors of breast cancer among Iraqi Kurdish women as well as to investigate the effect of some Mediterranean food items on this issue. Materials and Methods: This retrospective case-control study was constructed in Sulaimanyah governorate-Iraq. Data were collected regarding socio-demographic characters, established risk factors, and dietary habits of 338 cases that were registered in Sulaimanyah Breast Center during January 2015-February 2019 with collection of same items for 338 age-matched controls. Results: The marriage was appeared to be a protective factor with (OR = 0.596, CI: 0.364-0.974, P = 0.039). Age at menarche ≥14 years has a protective effect with (OR: 0.326, P = 0.027) and 152 cases (45.0%) had menarche at ≤12 years compared to 56 controls (16.6%) with (P = 0.000). Numbers of children ≥ 3, regular exercise, and breastfeeding for >48 months duration have protective role. Consumption of fast foods and some Mediterranean foods weekly >2 times are risk factors, while taking stewed meat weekly one time, fish weekly ≥1 time, fruit daily>1 time and vegetables daily≥1 time, and black tea daily >3 cups have preventative effect on breast cancer. Conclusion: Among Kurdish women, some items of Mediterranean food have the same causative effect as fast food items. Marriages, consumption of stewed meat, fish, fruit, vegetables, and black tea may have preventative effect.